Chasing Gravitational Waves with the Cherenkov Telescope Array - Green, J.G.; Carlile, C.; Dravins, D. ; 0000-0001-9024-0400 (2024)
The detection of gravitational waves (GWs) from a binary neutron star (BNS) merger by Advanced LIGO and Advanced Virgo (GW170817), along with the discovery of the electromagnetic counterparts of this GW event, ushered in a new era of multimessenger astronomy, providing the first direct evidence that BNS mergers are progenitors of short gamma-ray bursts (GRBs). Such events may also produce very-high-energy (VHE, > 100GeV) photons which have yet to be detected in coincidence with a GW signal. The Cherenkov Telescope Array (CTA) is a next-generation VHE observatory which aims to be indispensable in this search, with an unparalleled sensitivity and ability to slew anywhere on the sky within a few tens of seconds. Achieving such a feat will require a comprehensive real-time strategy capable of coordinating searches over potentially very large regions of the sky. This work will evaluate and provide estimations on the number of GW-CTA events determined from simulated BNS systems and short GRBs, considering both on- and off-axis emission. In addition, we will present and discuss the prospects of potential follow-up strategies with CTA. © Copyright owned by the author(s) under the terms of the Creative Commons.
Keywords: Cerenkov counters; Cosmic ray detectors; Cosmology; Gravitational effects; Photons; Stars; Binary neutron stars; Cherenkov telescope arrays; Electromagnetics; Energy Observatory; Gamma rays bursts; Gravitational-wave signals; Gravitational-waves; Large regions; Real time strategies; Very high energies; Telescopes